1984
DOI: 10.1111/j.1476-5381.1984.tb10798.x
|View full text |Cite
|
Sign up to set email alerts
|

Mediators of the secretory response to kinins

Abstract: 1 The output of immunoreactive (i) 6 keto prostaglandin Fl, (i6ketoPGF1,). iPGE2 and ithromboxane B2 (iTXB2) from isolated colonic epithelium of the rat into the apical and basolateral bathing solution has been measured. In some instances tissues were also voltage clamped at 0 mV to measure short circuit current (SCC). 2 Kallidin (lysylbradykinin) stimulated the output of all three eicosanoids, specifically from the basolateral face of the tissue. The output was similar whether or not the tissues were short ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
26
0

Year Published

1984
1984
2012
2012

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 31 publications
(43 reference statements)
2
26
0
Order By: Relevance
“…In rat colon, kinin responses have been shown to be partially dependent upon eicosanoid formation (Cuthbert, Halushka, Margolius & Spayne, 1984b;Cuthbert, Halushka, Kessel, Margolius & Wise, 1984a) whereas in the epididymis the response to kinin on the basolateral side is completely abolished by piroxicam and indomethacin. Chronic treatment with PGE2 caused reduced fertility in male rats (Hib, Ponzio & Vilar, 1979) and the suggested mechanism was reduced sperm transit time caused by increased epididymal motility; thus the time available for sperm maturation was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…In rat colon, kinin responses have been shown to be partially dependent upon eicosanoid formation (Cuthbert, Halushka, Margolius & Spayne, 1984b;Cuthbert, Halushka, Kessel, Margolius & Wise, 1984a) whereas in the epididymis the response to kinin on the basolateral side is completely abolished by piroxicam and indomethacin. Chronic treatment with PGE2 caused reduced fertility in male rats (Hib, Ponzio & Vilar, 1979) and the suggested mechanism was reduced sperm transit time caused by increased epididymal motility; thus the time available for sperm maturation was reduced.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, PGE 2 release elicited by AITC (10 Ϫ4 M) has been reported in rat urinary bladder (3). In addition, other inflammatory mediator kinins are known to induce Cl Ϫ secretion through PGE 2 release in the colon (6, 36) independent of extracellular Ca 2ϩ (13). In the present study, we demonstrated that AITC-evoked anion secretion was independent of neural activity or extracellular Ca 2ϩ ( Table 3), suggesting that AITC-evoked anion secretion is mediated by PG release through a Ca 2ϩ -independent process.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of eicosanoid synthesis does not affect the calcium signal but severely attenuates the SCC response. Prostaglandins activate epithelial adenylate cyclase (Cuthbert et al, 1984) which in turn causes apical chloride channels to open (Henderson et al, 1992). Furthermore in Colony 29 epithelial cells, calcium release from intracellular stores provokes a further calcium influx from outside the cell .…”
Section: Discussionmentioning
confidence: 99%